2005
DOI: 10.1128/iai.73.7.4180-4189.2005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Helicobacter pylori Virulence Factors and Compounds on Activation and Maturation of Human Dendritic Cells

Abstract: Recently, we and others have shown that Helicobacter pylori induces dendritic cell (DC) activation and maturation. However, the impact of virulence factors on the interplay between DCs and H. pylori remains elusive. Therefore, we investigated the contribution of cag pathogenicity island (PAI) and VacA status on cytokine release and up-regulation of costimulatory molecules in H. pylori-treated DCs. In addition, to characterize the stimulatory capacity of H. pylori compounds in more detail, we studied the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
63
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 67 publications
11
63
2
Order By: Relevance
“…Different from the LPS of other gram-negative bacteria, H. pylori LPS failed to induce the expression of those molecules (data not shown). Recently, Kranzer et al reported that the level of expression of TNF-␣ was lower in human DC cells pulsed with H. pylori WCS than in those pulsed with LB or FKB (19), which contradicts our result. The difference is probably due to the fact that they used human DCs which probably comprised a heterologous DC population rather than myeloidtype DCs selected with CD11b.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Different from the LPS of other gram-negative bacteria, H. pylori LPS failed to induce the expression of those molecules (data not shown). Recently, Kranzer et al reported that the level of expression of TNF-␣ was lower in human DC cells pulsed with H. pylori WCS than in those pulsed with LB or FKB (19), which contradicts our result. The difference is probably due to the fact that they used human DCs which probably comprised a heterologous DC population rather than myeloidtype DCs selected with CD11b.…”
Section: Discussioncontrasting
confidence: 99%
“…For the pulsing of Jaws II cells with H. pylori-related antigens, ca. 100 l (WCS preparation) to 200 l (LB and FKB preparations) of H. pylori-related antigens was added to 60 to 80% confluent Jaws II cells in a 6-well culture plate and incubated at 37°C for 48 h. (8,19). The clonal proliferation of T cells exposed to LB-, FKB-, and WCS-pulsed Jaws II cells was assayed using 5-bromo-2Ј-deoxyuridine (BrdU) (15) and compared to that of T cells exposed to unpulsed Jaws II cells.…”
Section: Dcsmentioning
confidence: 99%
“…In addition, we determined that the genotypes 1, 2, 3, and 4 had stimulated the secretion of IL-1β, IL-6, TNF-α, and IL-10 with different levels. Thus, our findings were similar with the previous studies (10,14,33,39,41,42).…”
Section: Discussionsupporting
confidence: 93%
“…Kranzer et al (39) reported that the cagA and vacAs2/m2 positive H. pylori strains induced the most prominent elevations of IL-1β, IL-6, IL-8, IL-12, TNF-α, and IL-10 in dendritic cells. Schmidt et al (10) reported that the cagA and vacAs2/m2 positive H. pylori strains induced low levels of IL-8 secretion in AGS cells.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori continually stimulates gastric epithelial cells and infiltrating neutrophils, macrophages, and other lymphocytes to release proinflammatory cytokines, which enhance the inflammatory response (60,66,152). H. pylori recombinant urease is a potent stimulator of IL-12 and IFN␥ secretions from peripheral blood mononuclear cells (97), and when dendritic cells are cocultured with H. pylori, they secrete proinflammatory IL-6, IL-8, IL-12, IL-1␤, and TNF␣ (65,84) (Fig. 1).…”
Section: Chronic Inflammation and H Pylori-associated Diseasementioning
confidence: 99%